Akhlak Terpuji dan Implementasinya di Masyarakat - Agus Syukur (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2020)
ABSTRACTMorals are traits that grow in the human nature. These traits are united in him, so that it becomes the behavior of everyday life. From these morals, it is hoped that humans will be able to implement it into everyday life in the form of morals towards Allah SWT, morals towards the Prophet Muhammad, morals towards oneself, morals towards family, morals towards society, and morals towards the environment.Keywords : Akhlakul Mahmudah, Daily  Behavior, and Moral Implementation.